SOSIOKULTURAL PEMAIN SEPAKBOLA DITINJAU DARI KNOWLEDGE, AWARENESS DAN SKILLS TO INTERACT - Imron Dipraja, - (2019)
This research aims to find out the socio-cultural picture of soccer players in terms of awareness, knowledge and skills to interact in the training of Persib. The research method used is descriptive. The population and sample of the study were football players training for Persib aged 16-19 years. Sampling was done by technique (saturated sampling) samples in this study as many as 30 people. The analysis technique used is descriptive statistical analysis. The results showed that the sociocultural players were in the good category, in detail the indicators are as follows awareness playerwas in the good category, knowledge playerwas in the good category, and the skills to interact the players were in the sufficient category. The general picture can be said that the sociocultural level of football players in the Persib training program is in the Good category.